A bedaquiline/clofazimine combination regimen might add activity to the treatment of clinically relevant non-tuberculous mycobacteria. (10th January 2019) - Ruth, Mike Marvin; Sangen, Jasper J N; Remmers, Karlijn; Pennings, Lian J; Svensson, Elin; Aarnoutse, Rob E; Zweijpfenning, Sanne M H; Hoefsloot, Wouter; Kuipers, Saskia; Magis-Escurra, Cecile; Wertheim, Heiman F L; van Ingen, Jakko
Abstract: Background: Non-tuberculous mycobacteria (NTM) infections are hard to treat. New antimicrobial drugs and smarter combination regimens are needed. Objectives: Our aim was to determine the in vitro activity of bedaquiline against NTM and assess its synergy with established antimycobacterials. Methods: We determined MICs of bedaquiline for clinically relevant NTM species and Mycobacterium tuberculosis by broth microdilution for 30 isolates. Synergy testing was performed using the chequerboard method for 22 reference strains and clinical isolates of Mycobacterium abscessus (MAB) and Mycobacterium avium complex (MAC) . Time–kill kinetics (TK) assays with resistance monitoring of bedaquiline alone and combined with clofazimine were performed for MAB CIP 104536 and M. avium ATCC 700898; bedaquiline/clarithromycin combinations were evaluated against M. avium ATCC 700898. Interactions were assessed for TK experiments based on Bliss independence. Results: Bedaquiline had modest activity against tested NTM, with MICs between <0.007 and 1 mg/L. Bedaquiline showed no interaction with tested drugs against MAB or MAC. Lowest mean fractional inhibitory concentration index (FICI) values were 0.79 with clofazimine for MAB and 0.97 with clofazimine and 0.82 with clarithromycin for MAC. In TK assays, bedaquiline showed a bacteriostatic effect. Clofazimine extended the bacteriostatic activity of bedaquiline against MAB and yielded a slight bactericidal effect against M. avium . The bedaquiline/clofazimine combination slowed emergence of bedaquiline resistance for M. avium but promoted it for MAB. Relative to Bliss independence, bedaquiline/clofazimine showed synergistic interaction over time for MAB and no interaction for M. avium and bedaquiline/clarithromycin showed antagonistic interaction for M. avium . Conclusions: Following these in vitro data, a bedaquiline/clofazimine combination might add activity to MAB and MAC treatment. The bedaquiline/clarithromycin combination might have lower activity compared with bedaquiline alone for MAC treatment.